Análisis del modelo matemático de una celda de combustible de óxido sólido (SOFC) empleando como combustible el gas de síntesis, producido en la gasificación de biomasa (2017)
The present project focused on evaluating, through a mathematical model, an alternative for the use of a synthesis gas produced by the gasification of residual agricultural biomass. Said synthesis gas that is obtained at high temperatures, can be used as fuel for the solid oxide fuel cells (SOFC), in order to reduce losses of thermal energy in the cooling of the gas to be used in combustion engines Internal. It was estimated by mathematical modeling the electric potential that could be generated in a solid oxide fuel cell that is fed by a synthesis gas, the behavior in the anode and the cathode was evaluated, based on the electrochemical reaction that Occurs at the interface between the anode and the electrolyte, in which the compositions of the fuel (H2) were determined, and by means of these, the theoretical electric potential generated by a solid oxide fuel cell was estimated, taking into account the Transfer of electrons at the anode.